Serum lactate dehydrogenase as an early diagnostic biomarker to differentiate respiratory distress syndrome from transient tachypnea of the newborn - Umran, Raid M. R.; Abd, Karar A. (International Journal of Contemporary Pediatrics, 2026)
Background: Early differentiation between respiratory distress syndrome (RDS) and transient tachypnea of the newborn (TTN) remains clinically challenging, particularly in settings where imaging and advanced diagnostics may be delayed. Lactate dehydrogenase (LDH) is a marker of cellular injury and hypoxic stress and may assist in early etiologic discrimination. Objectives of the study were to evaluate the diagnostic performance of serum LDH measured within the first 12 hours of life in differentiating RDS from TTN, and to examine whether LDH provides independent diagnostic value beyond gestational age and birthweight. Methods: In this prospective diagnostic study, 151 neonates were enrolled: 50 normal controls, 63 with TTN, and 38 with RDS. Serum LDH levels were measured within 12 hours of birth. Group comparisons were performed using appropriate parametric or non-parametric tests. Diagnostic performance was assessed using receiver operating characteristic (ROC) analysis. Univariable and multivariable logistic regression models were constructed to evaluate the independent association of LDH with RDS. Results: LDH levels differed significantly across groups, demonstrating a stepwise increase from normal neonates to TTN and RDS (p<0.001). In symptomatic infants (TTN versus RDS), LDH showed good discriminatory accuracy (AUC=0.84; 95% CI: 0.75–0.92). A cutoff of 657 U/l yielded 97.4% sensitivity and 69.8% specificity. In univariable analysis, LDH predicted RDS (OR per 100 U/l=1.25; 95% CI: 1.08–1.45; p=0.003). However, after adjustment for gestational age and birthweight, LDH was no longer independently associated with RDS. Conclusions: Serum LDH demonstrates good early discriminatory performance for differentiating RDS from TTN and shows a biologically plausible gradient across disease severity. However, its association is largely mediated by prematurity and illness severity. LDH may serve as a useful adjunctive biomarker but should be interpreted in conjunction with perinatal and clinical parameters.